Биотехнологические подходы к улучшению хозяйственно-ценных признаков тритикале - Дубовец, Н.И.; Сычева, Е.А.; Бондаревич, Е.Б.; Соловей, Л.А. (Фактори експериментальної еволюції організмів, 2015)
Aims. Development of triticale secondary recombinant gene pool for use in breeding for semidwarfness and resistance to pre-harvest sprouting. Methods. Chromosome-engineering technologies in combination with molecular-cytogenetic and DNA labelling of genotypes. Results. Hybridization of substituted 6x-triticale forms with modern crop cultivars was carried out. Eight stable recombinant lines with different D(A)- and D(B)-chromosome sunstitutions were selected out of hybrid populations F4 by chromosome differential Giemsa staining (C-banding). Allelic composition of genes affecting formation of semidwarfness (Rht-B1, Rht8) and resistance to pre-harvest sprouting (Vp-1B) was investigated in the selected forms. Conclusions. A high frequency of D-genome chromosome inclusion in karyotype of triticale cultivars and dependence of the effectiveness of the introgression process on the genotypic environment of the developed hybrid form were revealed. Recombinant triticale lines, promising for breeding, were selected according to the data of moleculargenetic analysis. Keywords: triticale, chromosome-substitution lines, semidwarfness, resistance to pre-harvest sprouting, molecular markers.